Kompetensi sosial guru BK/konselor sekolah: Studi deskriptif di SMAN se-kota Denpasar - I Wayan Juliawan; Dewa Gede Eka Sastra Wiguna; Pande Wayan Bawa (Indonesian Journal of Educational Development, 2020)
This study aims to determine: 1) internal collaboration in the workplace by BK teachers/school counselors, 2) roles in the organization and professional activities of guidance and counseling by BK teachers/school counselors, 3) collaboration between professions by BK teachers/school counselors. This research is a quantitative descriptive research. This research was conducted at the Senior High School of Denpasar City. The subjects of this study were all BK counselors/counselors with an bachelor degrre of education background who served in the Senior High School of Denpasar City with a total of 20 people. The data collection method is in the form of a questionnaire. The data analysis technique used is descriptive analysis. The results showed that the indicator of internal collaboration in the workplace an average score of 4.06 with a percentage of 76.6% was in the quite good category. The indicators play a role in the professional organization of guidance and counseling with an average score of 4.29 with a percentage of 82% in the quite good category. On the collaboration indicator between professions the average score of 3.58 with a percentage of 64.7% is in the good category. Penelitian ini bertujuan untuk mengetahui: 1) kolaborasi intern di tempat kerja oleh guru BK/konselor sekolah, 2) peran dalam organisasi dan kegiatan profesi bimbingan dan konseling oleh guru BK/konselor sekolah, 3) kolaborasi antar profesi oleh guru BK/konselor sekolah. Penelitian ini merupakan penelitian deskriptif kuantitatif. Penelitian ini dilakukan di SMA Negeri se-kota Denpasar. Subjek penelitian ini adalah seluruh guru BK/konselor yang berlatar belakang pendidikan S1 BK yang bertugas di SMA Negeri se-kota Denpasar dengan jumlah 20 orang. Metode pengumpulan data berupa angket. Teknik analisis data yang digunakan adalah analisis deskriptif. Hasil penelitian menunjukkan bahwa indikator kolaborasi intern di tempat kerja skor rata-rata 4,06 dengan persentase 76,6% berada pada kategori cukup baik. Pada indikator berperan dalam organisasi profesi bimbingan dan konseling skor rata-rata 4,29 dengan persentase 82% berada pada kategori cukup baik. Pada indikator kolaborasi antar profesi skor rata-rata 3,58 dengan persentase 64,7% berada pada kategori baik.